The effect of football basic technical training using unilateral leg on bilateral leg transfer in male children - BOZKURT, SİNAN (My University, 2020)
This experiment investigted transfer of skills from dominant leg limb to non-dominant leg limb and vice versa in dribbling with the ball, juggling and passing/shooting technics of soccer for inexperienced male children. 24 male student age of 10 years from 3th grade who have not involved in a football club as a player. In football basic technical practices, dominant leg (DL) group just used their dominand leg/foot, and non-dominant leg (NDL) group  just used their non-dominant leg/foot. Practice phase applied one time a week between February and May on the football field with synthetic grass. The results showed there were not exist no significant difference between the transfers from dominant leg group to non-dominant group or vice versa. On the other hands, performance of all technics improved on dominant and non-dominant groups for the comparison of pre- and post-tests. The findings suggest that the transfer of learning skills could be more effective from non-dominant leg limb to dominant leg limb significantly for technics of juggling, dribbling and kicking.